Gabapentin for Off-Label Use: Evidence-Based or Cause for Concern? - Peckham, Alyssa M (Subst Abuse, 2018)
Gabapentin is widely used in the United States for a number of off-label indications, often as an alternative to opioid therapy. Increasing evidence has emerged suggesting that gabapentin may not be as benign as once thought and may be associated with substance abuse in concert with opioids. With concerns for safety mounting, it is prudent to examine the efficacy of gabapentin across its many uses to understand the risk-benefit balance. Reviews on off-label indications such as migraine, fibromyalgia, mental illness, and substance dependence have found modest to no effect on relevant clinical outcomes. This high-quality evidence has often been overshadowed by uncontrolled studies and limited case reports. Furthermore, the involvement of gabapentin in questionable marketing schemes further calls its use into question. Overall, clinicians should exercise rigorous appraisal of the available evidence for a given indication, and researchers should conduct larger, higher-quality studies to better assess the efficacy of gabapentin for many of its off-label uses.